First country record of trachycephalus mesophaeus (Hensel, 1867) (amphibia, anura, hylidae) in Argentina - García Marsa, Jordi Alexis (2020)
We report the first record of the Porto Alegre Golden-eyed Treefrog, Trachycephalus mesophaeus (Hensel, 1867), from Argentina based on a single specimen collected in the 1980s at Las Lomitas, province of Formosa, northeastern Argentina. This new record, within the Chacoan Biogeographical Region, is separated by more than 1300 km from its main range in the Atlantic Forest.